The Impact of the COVID-19 Pandemic on Urology Practice in Indonesia: A Nationwide Survey - Rasyid, Nur; Birowo, Ponco; Parikesit, Dyandra; Rahman, Fakhri (Urology Journal, 2020)
Purpose. This study aimed to investigate the impact of COVID-19 on urology practice in Indonesia. Material and Methods. This was a cross-sectional study using web-based questionnaire (Survey Monkey), which was distributed and collected within a period of three weeks. All practicing urologists in Indonesia were sent an e-questionnaire link via E-mail, WhatsApp Messenger application, and/or short message service, and the chief of residents in each urology centre distributed the e-questionnaire to urology residents. Results. The response rate was 369/485 (76%) among urologists and 220/220 (100%) among urology residents. Less than 10 percent of the responses in each section were incomplete. There are 35/369 (9.5%) of urologists and 59/220 (26.8%) of urology residents had been suspected as COVID-19 patients, of whom seven of them were confirmed to be COVID-19 positive. The majority of urologists (66%) preferred to continue face-to-face consultations with a limited number of patients, and more than 60% of urologists preferred to postpone the majority (66%) or all elective surgery. Most urologists also chose to postpone elective surgery in patient with COVID-19-related symptoms and patient who required post-operative ICU-care. Urologist and urology residents reported high rates of using personal protective equipment, except for medical gowns and N95 masks, which were in short supply. Several uro-oncology surgeries were considered to be the top priority for Indonesian urologist during COVID-19 epidemic period. Conclusion. The COVID-19 pandemic has caused a decline in urology service in both outpatient clinic and surgery services with uro-oncological procedure as a priority to conduct.